HNRNPA2B1: a novel target in pulmonary arterial hypertension - Yingying Wei; Daiqin Wu; Na Deng; Fujia Xu; Sihan Luo; Xinxin Fan; Haijun Guo; Jingjing Chen; Wei Li; Xiaoyun Si (Frontiers in Cardiovascular Medicine)
Purpose of ReviewPulmonary arterial hypertension (PAH) is a progressive clinical syndrome characterized by pulmonary vascular remodeling and elevated pulmonary artery pressure, associated with high morbidity and mortality. While targeted therapies have improved patient prognosis, restoring normal hemodynamics and reversing vascular pathology remain unmet challenges. Heterogeneous nuclear ribonucleoprotein A2/B1 (HNRNPA2B1), an RNA-binding protein integral to mRNA processing and post-transcriptional regulation, governs critical processes including cell proliferation, apoptosis, angiogenesis, and endothelial homeostasis. However, its role in PAH pathogenesis remains poorly defined. This review synthesizes current evidence on HNRNPA2B1 in PAH, evaluates its potential mechanistic contributions, and discusses therapeutic implications. Given the fact that much of the connections between PAH and HNRNPA2B1 are speculative, rigorous mechanistic studies are imperative to clarify its pathobiological relevance.Recent FindingsEmerging preclinical evidence suggests that HNRNPA2B1 silencing attenuates monocrotaline (MCT)-induced pulmonary hypertension (PH) in rat models. Mechanistically, HNRNPA2B1 modulates vascular smooth muscle cell (VSMC) proliferation via cross-talk between multiple signaling cascades and macrophage polarization dynamics, both central to pulmonary vascular remodeling. Nevertheless, clinical translatability remains uncertain, as no studies have yet conclusively validated HNRNPA2B1 as a druggable target in human PAH.SummaryRecent evidence suggests HNRNPA2B1 has emerged as a potential therapeutic target for PAH. However, further studies are essential to elucidate its role in modulating the pathogenic mechanisms underlying PAH.